Assessing the General Data Dissemination System-What Has Been Accomplished After Ten Years, and Where Do We Go From Here?. (Policy Papers; Policy Paper ;, 2008)
This paper reviews the role of the GDDS in helping developing and emerging market countries improve the dissemination of macroeconomic and sociodemographic data. It considers whether the GDDS, in the way it was designed about a decade ago and enhanced along the way, has fulfilled its purpose. Further, it considers whether the GDDS remains relevant to its current and prospective members, given ongoing global integration, increasing emphasis on transparency and governance mechanisms, and increased reliance on the Internet and electronic data transmission.